2022
DOI: 10.3389/fevo.2022.984384
|View full text |Cite
|
Sign up to set email alerts
|

Food web functional responses

Abstract: This article reviews the nature of functional responses that have commonly been used to represent feeding relationships in the ecological literature. It compares these with the range of functional response forms that are likely to characterize species in natural communities. The latter set of responses involves many more variables. The article reviews the history of functional response models, and examines previous work that has allowed the functional response of a predator to a single type of prey to depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 94 publications
0
24
0
Order By: Relevance
“…Theoretical studies have shown that variations in the shape of the functional response can have important ecological consequences for the structure and dynamics of communities by altering the coexistence among prey, and the strength and signs of the interactions among them (Abrams and Cortez, 2015; Abrams et al, 1998; Abrams and Matsuda, 2004; Brose et al, 2006; Coblentz, 2020). However, very few empirically-based multi-species functional responses were developed (Abrams, 2022; DeLong, 2021). The evaluation of functional response using phenomenological models often fail to discriminate between different response shapes (Novak and Stouffer, 2020), which makes it difficult to quantify the strength of predator-mediated interactions in the wild.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Theoretical studies have shown that variations in the shape of the functional response can have important ecological consequences for the structure and dynamics of communities by altering the coexistence among prey, and the strength and signs of the interactions among them (Abrams and Cortez, 2015; Abrams et al, 1998; Abrams and Matsuda, 2004; Brose et al, 2006; Coblentz, 2020). However, very few empirically-based multi-species functional responses were developed (Abrams, 2022; DeLong, 2021). The evaluation of functional response using phenomenological models often fail to discriminate between different response shapes (Novak and Stouffer, 2020), which makes it difficult to quantify the strength of predator-mediated interactions in the wild.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Abrams (2022), our understanding of numerical responses is much more limited than functional responses. To date, the numerical response is typically modeled through demographic processes in classical models (see MacArthur-Rosenzweig equations; Rosenzweig and MacArthur 1963).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive work in behavioral ecology and neuroscience challenges this theoretic assumption. Taking behavioral mechanisms, like the following, into account will increase the accuracy of predator-prey models (Lima, 2002;Hacini et al, 2021;Abrams, 2022Abrams, ). 10.3389/fnbeh.2023…”
Section: Introductionmentioning
confidence: 99%